An Introduction to Particle Physics and the Standard Model - Mann, Robert (Taylor & Francis, 2021)
An Introduction to the Standard Model of Particle Physics familiarizes readers with what is considered tested and accepted and in so doing, gives them a grounding in particle physics in general. Whenever possible, Dr. Mann takes an historical approach showing how the model is linked to the physics that most of us have learned in less challenging ar